Pengaruh Perbandingan Jagung Manis dan Kacang Tanah Terhadap Karakteristik Susu Jagung Modifikasi - Urziah, Nuhayillah; Yusa, Ni Made; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This study aimed to determine the effect of the sweet corn and peanut ratio on the characteristics of modified corn milk and to find out the right amount of sweet corn and peanuts to obtain the best characteristics of the modified corn milk. The experimental design used was a completely randomized design with the comparison of sweet corn and peanuts as a treatment which consisted of 6 levels, namely: 100%:0%, 90%:10%, 80%:20%, 70%:30%, 60% :40%, and 50%:50%. The treatment was repeated 3 times, resulting in 18 experimental units. The data obtained were analyzed by analysis of Variance, and if the treatment had a significant effect, it would be continued with the Duncan Multiple Range test. The results showed that the comparison of sweet corn and peanuts had a significant effect on moisture content, ash content, protein content, fat content, carbohydrate content, total solids content, crude fiber content, beta carotene, hedonic test (color, aroma and overall acceptance) and scoring test (color, aroma and taste). However, it had no significant effect on the hedonic taste test. The best characteristics were obtained from the ratio of 70% sweet corn: 30% peanuts with the criteria of water content 85.32%, moisture content 0.11%, protein content 2.76%, fat content 6.43%, carbohydrate content 5.63%, total solids content 14.68 %, crude fiber content of 2.26% and beta carotene content of 0.08% as well as the sensory properties of the hedonic test the color was favored with the criteria of white and slightly yellow, the aroma and taste were typical of peanuts and overall acceptance was liked.